Computational and Physical Modeling for Multi-Cellular Pneumatic Envelope Assemblies. (June 2015) - Velikov, Kathy; Thün, Geoffrey; O'Malley, Mary; Junghans, Lars
This article describes recent research on the performative, formal and aesthetic potentials of multi-cellular pneumatic foil-based envelope systems for lightweight, responsive building skins able to control thermal insulation and air exchange with minimal amounts of energy and mechanical components. The prototype-based research involves the use of principles from biological examples of pneus, which inform the design of physical analogue models at an architectural scale. The process entails physical-computational feedback loops wherein physical performance findings are fed into computational design models for pneumatics and membranes, as well as modified energy models, in order to advance the predictive design capacities of simulation tools in designing such systems. In this process, material agency allies with computational agency to develop novel possibilities for dynamic pneumatic envelopes.